1993
DOI: 10.1063/1.530257
|View full text |Cite
|
Sign up to set email alerts
|

Finiteness of physics and its possible consequences

Abstract: The modular analog of representations of the so(1,4) algebra for a system of two spinless particles is considered in the framework of approach (proposed by the author earlier), in which physical systems are described by the elements of a linear space over a finite field, and operators of physical quantities by linear operators in this space. The eigenvalues of the free mass operator and corresponding eigenvectors are found. It is shown that if the finite field under consideration satisfies some properties then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(80 citation statements)
references
References 18 publications
2
78
0
Order By: Relevance
“…However, as shown in Refs. [2,3], in FQT the situation is similar to that in dS theory rather than in AdS theory.…”
Section: Remarks On Fundamental Theoriesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, as shown in Refs. [2,3], in FQT the situation is similar to that in dS theory rather than in AdS theory.…”
Section: Remarks On Fundamental Theoriesmentioning
confidence: 97%
“…As shown in Ref. [2] and in chapters 4 and 8 of Ref. [3] Statement 2: For algebra (2) there exist sets S and representations such that basis vectors in the representation spaces are eigenvectors of the operators from S with eigenvalues belonging to Z.…”
Section: Proof Of the Main Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,[9][10][11] (where we discussed different properties of dS quantum theory), shows that in the dS case the classical relative acceleration of two free particles is . From the formal point of view, the result is the same as in GR on dS space.…”
Section: Quantum Approach To Cosmological Accelerationmentioning
confidence: 99%
“…In Refs. [2,3] we have proposed an approach called GFQT where quantum theory is based on a Galois field with characteristic p. It has been shown that in the formal limit p → ∞ GFQT recovers the predictions of standard continuous theory. Then the fact that standard mathematics describes many experiments with a high accuracy can be explained as a consequence of the fact that in real life the number p is very large.…”
mentioning
confidence: 99%